Justice for Earthlings : Essays in Political Philosophy / [electronic resource] - Miller, David (Cambridge : Cambridge University Press, 2013)
In the past few decades social changes have impacted how we understand justice, as societies become both more multicultural and more interconnected globally. Much philosophical thought, however, seems to proceed in isolation from these developments. While philosophers from Plato onwards have portrayed justice as an abstract, universal ideal, Miller argues that principles of justice are always rooted in particular social contexts, and connects these ideas to the changing conditions of human life. In this important contribution to political philosophy, it is argued that philosophers need to pay more attention to the way that people actually think about what's fair, and only defend principles that are feasible to apply in the real world. To understand equality of opportunity, for example, we must explore the cultural constraints that people face when presented with life choices. Justice for Earthlings also explains how national boundaries make justice at global level different from social justice.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Justice